Geographical and ecological distribution of native bamboo species in San Luis Potosí, Mexico - Armendáriz, Natalia María Cruz; Reyes-Agüero, Juan Antonio; Ruiz-Sanchez, Eduardo; Martínez, Javier Fortanelli; Armendáriz, Fernanda Martínez (Phytotaxa, 2022)
Prior to this study, only four native bamboo species: Guadua longifolia, G. velutina, Lithachne pauciflora and Olyra latifolia, had been recorded in the state of San Luis Potosí, Mexico. However, the ecological and geographical distribution of those species were unknown. Two questions are addressed in this study: How many native bamboo species are there in San Luis Potosí? and, what is the geographical and ecological distribution of those species? The botanical exploration was carried out in 2019 and 2020. The geographical and ecological distribution was determined with a record of herbaria specimens and a botanical exploration. Multivariate methods and a similarity index were used to analyze the information of bamboo species in 13 sub-basins of the Huasteca Potosina (HP). The study registered seven native species, of which five are woody species: Chusquea enigmatica, Guadua aff. longifolia, G. velutina, Otatea acuminata and Riphidocladum racemiflorum, and two are herbaceous species: Lithachne pauciflora and Olyra latifolia. The study also found that G. velutina is the most frequent native species in the study area, registered in 12 of the 13 sub-basins mapped. The species with the least frequency were C. enigmatica and O. acuminata, registered in only one sub-basin each. The sub-basins with the highest richness were located in a strip along the slopes of the Sierra Madre Oriental (the SMOR). The seven native bamboo species in San Luis Potosí are distributed in the HP region, from the windward side of the SMOR to its extension to the Gulf Coastal Plain (GCP), in an elevation range of 15–1815 m asl. These seven native species are distributed throughout the SMOR, whereas the G. velutina predominates in GCP. The distance from water bodies is a determining factor in the distribution of species, especially G. velutina, identified in the present study as a riparian species.